The relationship between nurse staffing levels and objective and subjective quality of care: A panel data approach for Germany - Boris Augurzky; Christian Bünnings; Ansgar Wübker (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
In this study we investigate the relationship between nursing staffing levels and hospital quality in Germany. We use administrative data from almost all German hospitals from 2002 to 2013 and link it to mortality rates and patient satisfaction measures. To analyze the association between nursing staffing levels and hospital quality indicators empirically, we estimate linear regression models and control for a wide range of hospital and patient characteristics that might bias the results. In addition, we exploit the longitudinal structure of the data and rule out potential bias due to time-invariant unobserved heterogeneity. The estimation results indicate a positive relationship between nurse staffing levels and hospital quality for both subjective and objective quality measures. Increasing nurse staffing levels by 10 percent reduces the mortality rate by 0.05 percent and increases patient satisfaction by around 0.7 percent, on average. Although we find some of these relationships to be statistically significant, at least marginally, the absolute magnitudes of the estimated coefficients are rather small. – – In dieser Studie untersuchen wir den Zusammenhang zwischen der Pflegepersonalausstattung und der Qualität in deutschen Krankenhäusern. Dazu verwenden wir administrative Daten für fast alle Krankenhäuser in Deutschland im Zeitraum von 2002 bis 2013 und verknüpfen diese mit Sterblichkeitsraten und Patientenzufriedenheiten. Um den Zusammenhang zwischen der Pflegepersonalausstattung und den Qualitätsmaßen empirisch zu schätzen, verwenden wir ein lineares Regressionsmodell und kontrollieren für eine Vielzahl von Krankenhaus- und Patientencharakteristika, welche die Ergebnisse verzerren könnten. Zusätzlich nutzen wir die Längsschnittstruktur der Daten, um Verzerrungen durch zeitinvariante unbeobachtbare Heterogenität auszuschließen. Die Schätzergebnisse deuten an, dass es einen positiven Zusammenhang zwischen der Personalausstattung in der Pflege und den objektiven und subjektiven Qualitätsmaßen gibt. Eine Erhöhung der Pflegepersonalausstattung um 10 Prozent führt demnach durchschnittlich zu einer Reduktion in der Sterblichkeitsrate um 0,05 Prozent und einem Anstieg in der Patientenzufriedenheit von etwa 0,7 Prozent. Obwohl einige dieser Zusammenhänge statistisch signifikant sind, zumindest marginal, ist die absolute Größe der geschätzten Koeffizienten eher klein.
Keywords: C23; I11; I18; 330; Hospital quality; nurse staffing; patient satisfaction; mortality rate